AI and BI Synergy: A New Frontier in Business and Economics - Mazher, Muhammad Ahmad (UMT Artificial Intelligence Review, 2024)
The convergence of Artificial Intelligence (AI) and Business Intelligence (BI) is creating a new era of transformative change in the realms of business and economics. The current study aimed to combine AI with standard BI approaches in order to achieve results, such as enhanced decision-making, optimized operations, and a competitive edge. The merger of BI and AI helps organizations and businesses derive deeper insights while using big datasets, which may cause improvements in predictive skills, personalized customer experiences, and ultimately optimized allocation of available resources. Moreover, this study also examined the prior literature and founded on observations, investigated the interaction of BI and AI with economics and areas pertaining to business study areas. After establishing and executing prior literature reviews and analytical structures, we concluded that the AI and BI combination is necessary and meaningful for the analysis of economic issues as well as business problems. In the current era, AI and BI interventions can generate complex challenges, daily threats, and innovative ideas. The study revealed a positive and significant influence of BI and AI’s positive and significant influence in resolve economic and business challenges and making decision-making an efficiently.